Circulating immune complexes and complement concentrations in patients with alcoholic liver disease. Issue 4 (April 1982) - Gluud, C; Jans, H
Abstract : A prospective evaluation of circulating immune complexes (CIC) and the activity of the complement system was undertaken in 53 alcoholic patients just before diagnostic liver biopsy. Circulating immune complexes were detected in 39% of patients with alcoholic steatosis (n = 26), 58% of patients with alcoholic hepatitis (n = 12), and 60% of patients with alcoholic cirrhosis (n = 15). No significant difference was found between the three group of patients. The activity of the complement system was within reference limits in the majority of patients and only slight differences were detected between the three groups. No significant differences were observed in liver biochemistry and complement concentrations in CIC-positive and CIC-negative patients. Detection of CIC in patients with alcoholic liver disease does not seem to be of any diagnostic value or play any pathogenic role. The high prevalence of CIC in these patients may be due to a depressing effect of ethanol on clearance of CIC or to increased immunological reactivity, or to both.